Poseidon principles: the impact on shipping finance - Boura, Georgia; Μπούρα, Γεωργία (2021)
Eleven major international credit-financial organizations, signed the “Poseidon Principles”, on 18th June 2019, a common framework of activity, according to which, the adaptation and enforcement of environmental principles and targets by the shipping companies form a strict condition under which further banking funding is provided. The framework, directly connected to the Annex VI MARPOL about air emissions and IMO’s Data Collection System, sets up an integrated process of linking banking financing to sustainability goals related to the environment’s protection. The 2008 financial crisis led to the need for more responsible lending procedures and control of the credit risk, and finally to a shrinkage of the banking funding. At the same time, high environmental requirements create additional costs for the shipping companies and turn them to alternative sources of financing, outside banking sector. The year 2019, when Poseidon Principles were launched, has been characterized by low bank-oriented financing to the shipping sector and rise of the Asian financiers. The study identifies key questions arising from the application of the Principles on an economic, financial and legal level. It also includes a specific statistical analysis of the Poseidon Principles application on the shipping companies’ financing through the year 2019 and an unprecedented, stock market based, research of the Poseidon Principles affection on the shipping companies’ shares value. The assimilation and the expansion of the Poseidon Principles are to be seen and analyzed in the near future.